2021
DOI: 10.1007/s13304-021-01175-4
|View full text |Cite
|
Sign up to set email alerts
|

Strong impact of sarcopenia as a risk factor of survival in resected gastric cancer patients: first Italian report of a Bicentric study

Abstract: Gastric cancer (GC) accounts for 4% of all cancers in Europe. Sarcopenia is a complex syndrome characterized by a loss of muscle mass and function associated with age, often present in neoplastic patients. Recently, several studies have shown a significant association between sarcopenia and poor prognosis in various pathological conditions. The current observational retrospective study investigates the association between sarcopenia and overall survival (OS) and recurrence-free survival (RFS) in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Only 13 included studies involving 5,803 patients explored the predictive role of pretreatment SMI for DFS ( 22 , 23 , 26 , 32 , 34 37 , 40 , 41 , 47 , 49 ). The pooled results indicated that lower pretreatment SMI was related with worse DFS (HR = 1.39, 95% CI: 1.13–1.69, p < 0.001; I 2 = 58.5%, p = 0.004) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 13 included studies involving 5,803 patients explored the predictive role of pretreatment SMI for DFS ( 22 , 23 , 26 , 32 , 34 37 , 40 , 41 , 47 , 49 ). The pooled results indicated that lower pretreatment SMI was related with worse DFS (HR = 1.39, 95% CI: 1.13–1.69, p < 0.001; I 2 = 58.5%, p = 0.004) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two Japanese studies showed that impaired fasting blood glucose and high haemoglobin A1c are associated with an increased risk of developing GC in HP-positive individuals ( 14 , 15 ). Lately, results from studies on sarcopenia and obese sarcopenia have strengthened the assumptions that a strong relationship exists between tissue and body composition and GC ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…'Marbling', or fat infiltration into muscle, lowers muscle quality and work performance. Studies to understand the pathogenesis of SO observed certain patterns of age-related changes in body muscle and fat composition [7].…”
Section: Introductionmentioning
confidence: 99%